The impact of creative thinking on competitive advantage field : Research for a sample of the competent authorities in Baghdad Governorate (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The study aims to investigate and measure the role of creative thinking as an independent variable in relation to competitive advantage as a dependent variable. To achieve accurate results, a comprehensive examination of the variables along with their sub-dimensions is essential. Specifically, fluency, flexibility, and originality have been adopted as sub-dimensions of the creative thinking variable, while cost, quality, flexibility, and delivery are considered sub-dimensions of the competitive advantage variable. To address the primary research problem, the key question is framed as: "To what extent can creative thinking contribute to achieving competitive advantage for the banks under study?" The research was conducted in several private banks located in Baghdad Governorate, namely Trans-Iraq Bank, Gulf Bank, United Bank, and International Bank. The administrative population under investigation comprised 123 individuals, from which a total sample of 114 respondents was selected based on statistical treatment. The researcher employed a descriptive analytical approach and utilized a questionnaire for data collection. Data analysis was conducted using the statistical programs SPSS (v.28) and AMOS (v.26). One of the significant findings of the study is the presence of a statistically significant effect of creative thinking on competitive advantage.